Heterosis for economic traits in coconut (Cocos nucifera L.) - Shinde, V V; Ghavale, S L; Maheswarappa, H P; Jerard, B A; Sumitha, S (Journal of Plantation Crops, 2018)
Field studies conducted for a period of 12 years to assess the traits responsible for yield performance and heterosis of twelve coconut hybrids in comparison with three varieties showed that among the hybrids, GBGD x ECT recorded the highest mean yield of 127.6 nuts palm-1 year-1 and was on par with ECT x GBGD (106.9 nuts palm-1 year-1), COD x LCT (108.0 nuts palm-1 year-1) and WCT x MYD (107.6 nuts palm-1 year-1). Hybrid GBGD x PHOT recorded the highest fruit length (23.9 cm) followed by ECT x GBGD (23.3 cm). The hybrid ECT x GBGD recorded the highest values for most of the fruit characteristics viz., fruit breadth (17.3 cm), fruit weight (1180.0 g), husked fruit weight (758.0 g) and copra weight (231.1 g). The variety ‘Laccadive Ordinary’ recorded higher oil content (71.1%) compared to its hybrids, LCT x GBGD (70.8%), COD x LCT (70.0%) and LCT x COD (69.8%). Hybrids displayed substantial differences in their heterotic response for nut characters. The highest yielding hybrid, GBGD x ECT excelled its standard check by 40.8 per cent followed by LCT x COD (39.4%).